Sequência didática para o estudo de uma fórmula de Euler relativa a probabilidade - Batista, Ana Cristina Mascarenhas Nascimento (2024)
This work addresses the teaching-learning process in Mathematics applied to a didactic sequence for the study of an Euler formula relating to Probability. The approach is based on the use of digital teaching resources, the use of the history of mathematics and the construction of a direct mathematical demonstration. The use of digital resources enhances learning, as it favors communication between those who teach and those who learn. The history of Mathematics can make this subject more attractive and interesting, as it acts as a motivating element, which favors students’ initiation into research activities and facilitates the understanding of concepts. Contact with mathematical demonstration makes it possible to understand the particularities of the language of this science, as well as the perception of the need for its use.